Transorbital Neuroendoscopic Management of Sinogenic Complications Involving the Frontal Sinus, Orbit, and Anterior Cranial Fossa - Lim, Jae H.; Sardesai, Maya G.; Ferreira, Manuel, Jr.; Moe, Kris S. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Transnasal endoscopic surgery has remained at the forefront of surgical management of sinogenic complications involving the frontal sinus, orbit, and anterior skull base. However, the difficulty in accessing certain areas of these anatomical regions can potentially limit its use. Transorbital neuroendoscopic surgery (TONES) was recently introduced to transgress the limits of transnasal endoscopic surgery; the access that it provides could add additional surgical pathways for treating sinogenic complications involving the frontal sinus, orbit, and anterior cranial fossa. We describe a prospective series of 13 patients who underwent TONES for the management of various sinogenic complications, including epidural abscess, orbital abscess, and fronto-orbital mucocele or mucopyocele, as well as subperiosteal abscess presenting with orbital apex syndrome. The primary outcome measurement was the efficacy of TONES in treating these pathologies. TONES provided effective access to the frontal sinus, orbit, and the anterior cranial fossa. All patients demonstrated postoperative resolution of initial clinical symptoms with well-hidden surgical scars. There were no ophthalmologic complications or recurrence of pathology. Based on our experience, TONES appears to provide a valuable addition to the current surgical armamentarium for treating selected complications of sinusitis.
Keywords: transorbital; transpalpebral; transconjunctival; skull base; endoscopic; sinusitis complications; epidural abscess; orbital abscess; frontal sinus abscess; mucocele; mucopyocele; multiportal